Triagens de alta performance para a descoberta de agentes anti-Zika vírus - Dolci, Isabela (Universidade Federal de São Carlos, 2022)
The Zika virus (ZIKV) is an mosquito-borne transmitted by the bite of the Aedes aegypti mosquito, which became a public health problem during the 2015/2016 outbreak in the Americas and mainly in Brazil, where it was related to cases of microcephaly and Guillan syndrome. -Barré. The potential of the virus to re-emerge causing new epidemics is always latent, therefore, the search for effective treatments against viral infection becomes necessary, since there are still no vaccines or drugs available. The identification of antiviral agents quickly and efficiently depends on cellular/biochemical assays that can be performed in a high-throughput screening (HTS) mode. In this work, we used two HTS screening strategies to identify anti-ZIKV molecules. The first strategy was phenotypic, using cell assays based on replicon, a system in which the viral genome is modified by replacing structural proteins with a reporter gene. Thereby, there is no formation of new infecting viral particles, but the replication complex is kept fully functional. This approach was used to evaluate 560 molecules, among which 4 were able to inhibit the replication of the replicon, with Remdesivir being the most promising due to its high selectivity index (IS = 88.6). The second strategy was target-based and consisted of using the recombinant ZIKV protease, NS2B-NS3, expressed in bacteria and purified in 3 steps, to evaluate 4576 molecules in enzyme activity assays, which allowed the identification of 7 compounds capable of inhibit the enzyme by more than 80%. Both strategies proved to be very efficient for the proposed objectives, contributing to the advance in the search for potential anti-ZIKV agents. The next steps will be the confirmation of the inhibition of viral replication by the 4 compounds resulting from the phenotypic screening by quantification of the RNA replicon, using qRT-PCR, and also through viral infection assays through collaboration with Prof. Ana Carolina Jardim from the Federal University of Uberlandia (UFU). Regarding the compounds identified in the enzymatic assays, these will be validated in the cellular model expressing the ZIKV replicon.
High-throughput screening for discovery of anti-Zika virus agents
Keywords: Flavivírus; Zika; Drogas; Virus; NS2B; NS3; Enzymatic; Replicon; CIENCIAS BIOLOGICAS::BIOFISICA::BIOFISICA MOLECULAR